Gender and Governance: The Politics of Federalism in Malaysia - Cecilia Ng, (Kajian Malaysia, 2012)
The discourse on gender and governance has diverged in predominantly two separate directions. On the one hand, there is almost an exclusive discussion on women in politics where much of the focus is on the inclusion of women in the corridors of political power through the external utilisation of quotas in the electoral process. On the other hand, the literature on gender and organisations focuses on the inner mechanisms of the organisation without much attention to the broader political connections in society. This paper argues that both internal and external articulations are important and that attempts to examine these articulations in the context of the state of Penang, Malaysia, where the politics of federalism intersect with gender and governance issues at the level of local government are worth noting.